Patent foramen ovale: a potential source of cerebral embolism? - Schminke, Ulf; Ries, Stefan; Daffertshofer, Michael; Staedt, Ulrich; Hennerici, Michael G. (Cerebrovascular diseases, 1995)
Since the introduction of contrast transesophageal echocardiography (cTEE) and contrast transcranial Doppler sonography (cTCD) the incidence of patent foramen ovale (PFO) has increased, especially in young patients with stroke of unknown etiology. A hundred patients with cerebral ischemia (60 with otherwise unidentified origin and 40 with different sources of cerebral ischemia) were prospectively examined by both methods. cTCD was used in all patients for the detection of microbubbles (< 8 µm in diameter) monitored in both middle cerebral arteries after intravenous administration. cTEE studies were made in 65 patients. Both methods agreed in 55/65 (85%); a right-to-left shunt was observed in 21/65 (32%), negative results in 34/65 (52%). Discordance occurred in 10/65 (16 %); in 8/10, only cTCD revealed positive results probably due to small pulmonary arteriovenous shunts which were not visualized by cTEE. In total, a PFO was diagnosed in 41/100; in patients without source of cerebral ischemia, 33/60 (55%) had evidence of a PFO; in 8/40 (20%), the results contributed to the detection of multiple possible sources of cerebral ischemia.